The Relationship Between Religious/Spiritual Beliefs and Subjective Well-Being: A Case-Based Comparative Cross-National Study - Pérez, Sergio (Journal of religion and health, 2022)
The most unique aspect of religiosity/spirituality (R/S), supernatural beliefs, and their relationship with SWB has hardly been examined. This study explores the relationship between six R/S supernatural beliefs and SWB, in a case-based comparative cross-national design including two religious and two secular nations. Data were obtained from the International Social Survey Programme (ISSP) Religion IV module from the religious countries of the USA (n = 1060) and Turkey (n = 1353) and the secular countries of Denmark (n = 1281) and Czech Republic (n = 1112). SWB was measured as happiness and self-rated health. Statistical analyses were performed using binary logistic regression models replicated across countries. Results indicated that the American sample showed no evidence of relationships between R/S and SWB outcomes capable of improving the model over demographic and service attendance covariates. In Turkey, some R/S beliefs were found to be statistically significantly related to SWB, with positive and negative associations with happiness. No associations were found in the secular countries. Findings were discussed in the light of previous research and interpreted from a terror management theory perspective.